Early rituximab treatment is associated with increased and sustained remission in pemphigus patients: A retrospective cohort of 99 patients. Issue 5 (4th March 2022) - Nosrati, Adi; Mimouni, Tomer; Hodak, Emmilia; Gdalevich, Michael; Oren‐Shabtai, Meital; Levi, Assi; Mimouni, Daniel; Leshem, Yael A.
Abstract: Rituximab is the front‐line therapy for pemphigus disease. Although very effective, relapse rates are high. We assessed factors associated with disease remission and early relapse following the first rituximab cycle. A single center, retrospective cohort study of patients with pemphigus treated with rituximab (1000 mg 0, 14 days) at the Autoimmune Bullous Disease Clinic of the Division of Dermatology in Rabin Medical Center, Israel, between January 1, 1995 and March 31, 2020. The cohort included 99 patients with a median follow‐up of 37 months (range 12–155). After a single rituximab cycle, 74 patients (75%) achieved remission. Increased time to rituximab was associated with decreased remission rates (OR, 0.98 per month; 95% CI, 0.97–0.998). Of patients in remission with sufficient follow‐up, 15/69 (22%) experienced an early relapse (≤12 months from remission). Prolonged time to rituximab and increased baseline disease severity, were associated with early relapse (OR, 1.02 per month; 95% CI, 1.001–1.04; OR, 1.04 per point; 95% CI, 1.01–1.08, accordingly). Initiating rituximab early following diagnosis is recommended. Maintenance rituximab infusions, especially for patients with severe baseline disease, should be further investigated.